SISTEM PENDUKUNG KEPUTUSAN PENENTUAN INVESTASI KELAPA SAWIT DENGAN METODE INTERNAL RATE OF RETURN DALAM SATU BLOCK SAWIT DI LINGGA KUAMANG BUNGO JAMBI - Bambang Sudibyo; Joko Suismianto (Institut Teknologi Dirgantara Adisutjipto, 2015)
ABSTRACTTechnology developed in order to facilitate human work that would not be done manually, with the presence of the latest technologies that it is not a work of man may not be done quickly, accurately, and save time. One was for the manufacture of palm data processing applications that provide an overview to the public that it is feasible to plant palm oil or not to do, based on existing data and then recycled into Decision Support Systems. To process these data using the Internal Rate Of Return (IRR) as a method to make decisions based on data that have been processed. In this study processed data is the data of a group of Palm Jl. Salak Linga Kuamang Bungo Jambi. From the results of the data managed by the farmer group Palm block 22, Jalan Salak, Linga Kuamang, with interpolation of 30% per year, with a capital of USD 888,253,000.00 and generate income of Rp 2,063,387,050.00 in if using the Internal rate of Return produce interpolation (I) of 30, 113%. Since IRR> I, then it is worth to continue.